Photographic intervention effect on positive and negative affects during COVID-19: Mediating role of future self-continuity - Zhang, Feng; Pi, Yu; Li, Xiaobao (Frontiers in Psychology, 2023)
Meaning in Life (MIL) is a protective factor that buffers the impact of COVID-19 epidemic on emotions. Our study aimed to explore whether photographic intervention based on MIL could increase Positive Affect (PA) and mitigate Negative Affect (NA), and whether Future Self-Continuity (FSC) functioned as a mediator between them. In this study, 90 college students were randomly divided into an intervention group or a control group. Participants in the intervention group were asked to take a photo and describe it every two days lasting two weeks. All the participants in the two groups were measured by the Meaning in Life Questionnaire, Positive and Negative Affect Scale, and Future Self-Continuity Scale before and after the intervention. The results showed that: (1) Before the intervention, there were no significant differences in baseline levels of MIL, PA and NA, and FSC between intervention and control groups. (2) In the intervention group, compared to pre-test, the scores of MIL, PA, and FSC of post-test increased significantly, and the score of NA of post-test decreased significantly. (3) After the intervention, the scores of MIL, PA, and FSC in the intervention group were significantly higher than those in the control group; NA score in the intervention group was significantly lower than that in the control group. (4) In terms of the difference score (post-test minus pre-test), FSC was a mediator between MIL and PA. In conclusion, photographic intervention can effectively improve college students’ MIL, PA, and FSC while mitigating NA. Moreover, MIL can significantly enhance PA by the mediating role of FSC.